Pelatihan Public Speaking sebagai Upaya Peningkatan Keterampilan Komunikasi Siswa SMAN 63 Jakarta Melalui Metode Edukatif Partisipatif - Susanto , Rofian Dedi; Afriadi , Ido (Dharmahita: Journal of Community Service and Development, 2025)
Public speaking is an essential skill that students need to support their academic success and professional readiness in the future. This community service activity (PKM) aims to improve the communication skills of students of SMAN 63 Jakarta, especially in grades X and XI, through public speaking training based on participatory educational methods. The training was carried out in three main stages, namely the delivery of theoretical material, practical simulations, and feedback sessions. The results of the activity showed significant improvement in the aspects of self-confidence, ability to structure messages, and utilization of visual communication technology. The active participation of participants and the existence of reflective awareness are indicators of the success of the training. This activity also encouraged the formation of positive social interactions and collective values such as empathy and collaboration. With an approach that is contextual and relevant to the characteristics of Generation Z, this training proved effective in shaping integrated communication competencies. Therefore, public speaking training is recommended to be a routine school program integrated in student self-development and supported by continuous collaboration between schools and universities.